EFFECT OF APPLE ON FASTING BLOOD SUGAR AND PLASMA LIPIDS LEVELS IN TYPE II DIABETES - N. S. DANGE; KEDAR DESHPANDE (International Journal of Pharma and Bio Sciences, 2013)
Apple products have been shown to prevent skin, mammary gland and colon carcinogenesis in animal models. Epidemiological observations indicate that regular consumption of one or more apples a day may reduce the risk for lung and colon cancer. The present study investigated the potential effects of apples on fasting blood sugar and lipid parameters in Type II diabetics’ patients.Study includes 98 Type II diabetics’ patients attending diabetic OPD, which was divided into two groups. Type II diabetic (n=54) who were willing to take an apple in the diet daily, consider as subjects and remaining (n=44) Type II diabetics taken as controls. FBS and lipid profile were measured at baseline and after four weeks and compared to that of controls.FBS levels highly significant (p<0.0001) decreases in Type II diabetics as compared to controls. This finding also found when compared to age and sex wise. Fasting total cholesterol, triglycerides, LDL cholesterol were significantly decreases as compared to controls. HDL cholesterol significantly increases in Type II diabetics, who consumed apple. Present study revealed that one medium size apple in diet of Type II diabetics reduces the fasting blood sugar levels and lipid parameters which are beneficial for normal health of diabetics along with anti-diabetic drugs.